The Role of Social Responsibility of Sharia Financial Institution on Customer Loyalty - Sandra Dewi; Yaswirman Yaswirman; Rudi Febriamansyah; Henmaidi Henmaidi (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The form of customer support for Islamic financial services is very important to create resilience and competitiveness in the Islamic Financial Institution industry. By highlighting social activities, this paper tries to see the role of CSR of Islamic banks in influencing customer loyalty , both individually and through image, trust and service satisfaction. This path explores how CSR makes customers impressed, convinced, satisfied, amazed, and ultimately loyal to Islamic banks. Quantitative descriptive analysis shows that a) the role of CSR gives a positive perspective on customer loyalty, b) Corporate image does not have a significant effect on customer loyalty, c) Trust has a significant positive effect on customer loyalty, d) service satisfaction has a positive effect on service, e) simultaneously CSR, image, trust and service satisfaction have a significant effect on customer loyalty. Indirectly, CSR and loyalty have an interrelated and mutually beneficial relationship between financial institutions and customers. This research has resulted in a new study of the form of the role of CSR on customer loyalty to these financial institutions. The practical implication lies in the importance of developing CSR to generate trust and reputation which in turn increases customer loyalty to Islamic banks